A performance simulation tool for the analysis of data gathering in both terrestrial and underwater sensor networks - Ghaleb, Mukhtar; Felemban, Emad; Subramaniam, Shamala; Sheikh, Adil A.; Qaisar, Saad (Institute of Electrical and Electronics Engineers, 2017)
Wireless sensor networks (WSNs) have greatly contributed to human-associated technologies. The deployment of WSNs has transcended several paradigms. Two of the most significant features of WSNs are the intensity of deployment and the criticalness of the applications that they govern. The tradeoff between volume and cost requires justified investments for evaluating the multitudes of hardware and complementary software options. In underwater sensor networks (USNs), testing any technique is not only costly but also difficult in terms of full deployment. Therefore, evaluation prior to the actual procurement and setup of a WSN and USN is an extremely important step. The spectrum of performance analysis tools encompassing the test-bed, analysis, and simulation has been able to provide the prerequisites that these evaluations require. Simulations have proven to be an extensively used tool for analysis in the computer network field. A number of simulation tools have been developed for wired/wireless radio networks. However, each simulation tool has several restrictions when extended to the analysis of WSNs. These restrictions are largely attributed to the unique nature of each WSN within a designated area of research. In addition, these tools cannot be used for underwater environments with an acoustic communication medium, because there is a wide range of differences between radio and acoustic communications. The primary purpose of this paper is to present, propose, and develop a discrete event simulation designed specifically for mobile data gathering in WSNs. In addition, this simulator has the ability to simulate 2-D USNs. This simulator has been tailored to cater to both mobile and static data gathering techniques for both topologies, which are either dense or light. The results obtained using this simulator have shown an evolving efficient simulator for both WSNs and USNs. The developed simulator has been extensively tested in terms of its validity and scope of governance.